Prevalence of Oral Aphthous Stomatitis and Recurrent Herpes Labialis Among Dental Students - Hayder Mahdi Idan; Ghasaq Abdullah Mahmood; Ibtehal Qhtan Othman (Diyala Journal of Medicine, 2025)
Background: The most frequent oral mucosal lesion is recurrent aphthous stomatitis. It first appears in childhood or adolescence and is evident as many tiny, recurrent, or ovoid ulcers with yellow floors and erythematous haloes. A widespread viral infection, herpes labialis, is characterized by recurrent vesicular lesions, frequently on the lips and perioral tissue. Objectives: To find the prevalence of oral aphthous stomatitis and recurrent herpes labialis among dental students of Bilad Alrafidain University. Patients and Methods: A cross-sectional study was conducted among 187 dental students of Bilad Alrafidain University, who are in the fourth and fifth stages of the dental department. The data were collected using questionnaires. Questionnaires required two sections. The first section restricted personal information. The second section involved questions related to aphthous ulcers and recurrent herpes labialis, including the duration and site of the ulcer after examination. Results: In the present study, the number of students with aphthous ulcers in the fourth stage is 13 (14.1%), and in the fifth stage, 24 (25.3%), with a highly statistically significant difference. Out of 187 students, 10 (10.9%) had recurrent herpes labialis in the fourth stage, while 15 (15.8%) were in the fifth stage, indicating a highly significant statistical relationship. The number of students with recurrent aphthous stomatitis and recurrent herpes labialis in the fifth stage is 24 (25.3%) and 15 (15.8%), respectively, which is higher than in the fourth stage, where the numbers are 13 (14.1%) and 10 (10.9%), respectively, indicating a significant relationship. Conclusion: Recurrent aphthous stomatitis is a lesion with a higher prevalence in females than in males. Stress during the period of academic examinations is one of the reasons for recurrent eruption of aphthous stomatitis and reactivation of recurrent herpes labialis. Keywords: Aphthous stomatitis, Herpes labialis, Dental, Students, and Oral.